Developing an Extension Strategy for the Management and Eradication of Bush Encroachment in Communal Livestock Lands in Mopani District, Limpopo Province of South Africa (Research in Agriculture Livestock and Fisheries, 2026)
Bush encroachment poses a multifaceted challenge, driven by critical socio-economic, environmental, and governance factors within the communal livestock system. The article aimed to identify practical agricultural extension methods for combating bush encroachment on communal land. The study presents practical agricultural extension strategies for livestock farmers to address bush encroachment within the communal system. The study was conducted in the Mopani District with a sample of 300 communal livestock farmers. Quantitative data were analyzed using SPSS version 27, while qualitative data were analyzed using a thematic analysis framework. The findings highlight varied perspectives among livestock farmers, emphasizing the complexity of managing bush encroachment and the need for community-driven strategies. The study findings indicate that, while farmers possess relevant indigenous knowledge, the lack of structured extension support and technical training hinders the effective control of encroaching species. The study recommends integrating climate-smart agricultural practices, such as adaptive grazing, rangeland restoration, and climate-resilient land use. Additionally, it suggests creating a framework to formalize extension programs, define stakeholder roles, and improve land governance. This research enhances sustainable rangeland management by presenting a strategy for extension that is both context-sensitive and centered on communal livestock farmers.Res. Agric. Livest. Fish. Vol. 13, No. 1, April 2026: 01-21